Perancangan Sistem Informasi Retensi Rekam Medis di RS Paru Provinsi Jawa Barat - Jajang Somantri (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In the era of digitalization, technological developments are very influential in the health sector, one of which is in the medical record section. In its service, the place of service for the sick or commonly known as the Hospital utilizes information and communication technology called the Hospital Management Information System (SIMRS) which processes and integrates the entire flow of the hospital service process from patient registration to reporting to obtain information in a timely manner. precise and accurate. One example of a facility that applies SIMRS is the Lung Hospital of West Java Province, Sidawangi, Cirebon Regency, but it is still considered to be developed because of the unavailability of a retention feature that functions to reduce the number of medical records by sorting out inactive medical records. The manual method results in the medical records on the storage rack being over capacity and time-consuming. So, it is necessary to design a retention information system that is expected to be integrated with SIMRS. The purpose of this research is to produce an application using a website that is able to help sort out inactive medical records quickly and accurately. The system design uses the Extreme Programming method, because it is suitable for making simple applications. Making this application using PHP (Hypertext Preprocessor), database or database using MySQL which is a relational database management system, application for compiling text program text editor Visual Code Studio, and Bootstrap framework and web server source using XAMPP (Apache and MySQL). Keywords: Information Retention System, Extreme Programming, PHP, MySQL, Bootstrap